Konsepsi Bangunan Keluarga Sakinah Bagi Pasangan Suami Istri Yang Telah Bercerai Pada Masyarakat Muslim di Kota Manado - Ardianto Ardianto; Ridwan Jamal; Munir Tubagus (Jurnal Ilmiah Al-Syir'ah, 2017)
This study aims to describe the perception of married couples who have divorced to building harmonious family. The analysis is directed at the opinion of the informant research on the basic concept of harmonic family building which is understood to be glue of building harmonious family. This reserach is a case study using the qualitative approach. The results showed that couples who have been in Muslim Community in Manado city perceive that responsibility and mutual understanding, balance, and honesty is the foundation of harmonic family building.